Menarche among Peri-Natally HIV-Infected girls at the University of Nigeria Teaching Hospital, Ituku/Ozalla, Enugu, Nigeria - O A Iloh; A C Ubesie; K K Iloh; I J Emodi; A N Ikefuna; A C Ayuk (International Journal of Medicine and Health Development, 2017)
Background: Factors such as race, poverty, nutrition and chronic diseases have been shown to influence the age of attaining menarche in girls. HIV is one of the most prevalent chronic diseases among young girls living in sub-Saharan Africa. This study compares the age at onset of menarche between HIV-infected girls and un-infected controls matched for age and socio-economic status. Materials and Methods: A cross sectional study involving 100 HIV-infected girls aged 8-17 years and 100 un-infected counterparts matched for age and social class. Questionnaire was administered to study participants after obtaining consent from their caregivers. Age at attainment of menarche was obtained using recall method. Data analysis was done with SPSS version 20 (Chicago IL). Significant levels were assumed at p-values less than 0.05. Results: Eighty-seven subjects and controls respectively (87%) were within the age range of achieving menarche. Among them, 19 subjects (22%) and 31 controls (36%) had attained menarche ((OR= 0.505, CI= 0.258-0.988, p =0.046). Menarche occurred at a mean age of 12.84 ± 1.30 years among the subjects and 12.32 ± 0.79 years among the controls (p=0.085).Conclusions: A significant proportion of subjects compared to controls had achieved menarche.